Feminist encounters with Confucius - FOUST, Mathew (Institutional Knowledge at Singapore Management University, 2016)
This work builds on earlier works, which defend Confucianism against charges of sexism and present interpretations of Confucianism compatible with Feminism, but contributors go beyond the much discussed care ethics, and common arguments of how ren (humaneness) can ground an egalitarian humanism that include gender equality. Besides ethics and political philosophy topics, this volume includes discussions in other philosophical areas such as epistemology, metaphysics, and applied philosophy. Through the encounter of Feminism and Confucius’s perspectives, each contributor generates novel answers to the questions addressed. In some cases, authors raise new questions about the chosen topic, inadequacies in how it has been addressed in previous Confucian or Feminist discourse, and/or challenges for either or both Confucianism and Feminism.